Serum-free light chains in HIV-associated lymphoma: no correlation with histology or prognosis. (19th June 2015) - Tittle, Victoria; Rayment, Michael; Keeling, Emma; Gabriel, Ian; Yarranton, Helen; Bower, Mark
Abstract : Objectives: Serum-free light chains (sFLCs) are a biomarker of B-cell proliferation. Two case-control studies found elevated levels of polyclonal sFLCs predict the development of HIV-associated lymphomas (HALs) in people living with HIV. This effect appears greater for non-Hodgkin's lymphomas than Hodgkin's lymphoma. In this study, we measured sFLCs at diagnosis of HALs, and correlated levels with histology and survival. Methods: The clinic database of the National Centre for HIV Malignancy was used to identify HAL patients, in the antiretroviral treatment era. Levels of sFLCs were measured using stored sera (cases from 1996 to 2008) and prospectively from 2008 to 2014. Serum immunoglobulins were available for 201 patients. We assessed correlations between sFLCs, serum immunoglobulins, and histological subtypes and overall survival. Results: Two hundred and sixty-four patients were identified and 70% had polyclonal sFLC, 8% monoclonal sFLC (90% kappa sFLC), and 22% normal sFLC levels. No significant difference in sFLCs was observed between the three major histological subtypes of HAL (Hodgkin's lymphoma, diffuse large B-cell lymphoma, and Burkitt lymphoma). Elevated sFLCs did not influence overall survival in HAL or for the three subtypes individually. Discussion: Whilst these data confirm the finding of elevated sFLC in HAL, there was no significant difference in sFLC measurements between histological subtypes despite differences in pathogenesis. sFLC did not predict survival in HAL overall or by histological subtype. Elevated sFLCs may predict HAL, but measurement of sFLCs has limited utility in the classification and prognostication of these cases.